Ironic Characterization in the Works of S. Y. Agnon - Fuḳs, Ester (AJS review, 1982)
[Reb Zevi] saw and realized that the business was leading [Reb Issachar] astray, that he was being distracted by it and was distracting others, until finally he felt like one tugged by a distorted idea, a senseless bit of sophistry or vain embellishment, like one who becomes increasingly bogged down as he trudges from one pilpul to the next, from one piece of vanity to the next, until it finally drags him into a morass from which he can never emerge.